Hydrothermal frictional strengths of rock and mineral samples relevant to the creeping section of the San Andreas Fault. (August 2016) - Moore, Diane E.; Lockner, David A.; Hickman, Stephen
Abstract: We compare frictional strengths in the temperature range 25–250 °C of fault gouge from SAFOD (CDZ and SDZ) with quartzofeldspathic wall rocks typical of the central creeping section of the San Andreas Fault (Great Valley sequence and Franciscan Complex). The Great Valley and Franciscan samples have coefficients of friction, μ > 0.35 at all experimental conditions. Strength is unchanged between 25° and 150 °C, but μ increases at higher temperatures, exceeding 0.50 at 250 °C. Both samples are velocity strengthening at room temperature but show velocity-weakening behavior beginning at 150 °C and stick-slip motion at 250 °C. These rocks, therefore, have the potential for unstable seismic slip at depth. The CDZ gouge, with a high saponite content, is weak (μ = 0.09–0.17) and velocity strengthening in all experiments, and μ decreases at temperatures above 150 °C. Behavior of the SDZ is intermediate between the CDZ and wall rocks: μ < 0.2 and does not vary with temperature. Although saponite is probably not stable at depths greater than ∼3 km, substitution of the frictionally similar minerals talc and Mg-rich chlorite for saponite at higher temperatures could potentially extend the range of low strength and stable slip down to the base of the seismogenic zone. Highlights: Frictional properties of SAFOD gouges (CDZ, SDZ) and wall rocks diverge with heating. Great Valley sequence and Franciscan rocks may slip seismically at depth. The first heated friction data on a saponite separate are presented.